Bulk Incorporation with 4‐Methylphenethylammonium Chloride for Efficient and Stable Methylammonium‐Free Perovskite and Perovskite‐Silicon Tandem Solar Cells. Issue 9 (10th January 2023) - Duong, The; Nguyen, Thuan; Huang, Keqing; Pham, Huyen; Adhikari, Sunita Gautam; Khan, Motiur Rahman; Duan, Leiping; Liang, Wensheng; Fong, Kean Chern; Shen, Heping; Bui, Anh Dinh; Mayon, Azul Osorio; et al.
Abstract: Methylammonium (MA)‐free perovskite solar cells have the potential for better thermal stability than their MA‐containing counterparts. However, the efficiency of MA‐free perovskite solar cells lags behind due to inferior bulk quality. In this work, 4‐methylphenethylammonium chloride (4M‐PEACl) is added into a MA‐free perovskite precursor, which results in greatly enhanced bulk quality. The perovskite crystal grains are significantly enlarged, and defects are suppressed by a factor of four upon the incorporation of an optimal concentration of 4M‐PEACl. Quasi‐2D perovskites are formed and passivate defects at the grain boundaries of the perovskite crystals. Furthermore, the perovskite surface chemistry is modified, resulting in surface energies more favorable for hole extraction. This facile approach leads to a steady state efficiency of 23.7% (24.2% in reverse scan, 23.0% in forward scan) for MA‐free perovskite solar cells. The devices also show excellent light stability, retaining more than 93% of the initial efficiency after 1000 h of constant illumination in a nitrogen environment. In addition, a four‐terminal mechanically stacked perovskite‐silicon tandem solar cell with champion efficiency of 30.3% is obtained using this MA‐free composition. The encapsulated tandem devices show excellent operational stability, retaining more than 98% of the initial performance after 42 day/night cycles in an ambient atmosphere. Abstract : Adding 4‐methylphenethylammonium chloride into a 3D perovskite precursor results in better film quality with larger grains. Quasi‐2D perovskites are formed and passivate defects at the grain boundaries. The perovskite surface chemistry is modified, and the surface energies become more favorable for hole extraction. This approach leads to methylammonium‐free perovskite solar cells with a champion steady‐state efficiency of 23.7% and excellent stability.